The Effect of Eight Weeks of Rebound Therapy on Balance and Quality of Life in Patients with Parkinson's Disease - maryam fijani; gholamali ghasemi; ahmad chitzas (Shiraz University of Medical Sciences, 2024)
Background: Parkinson's disease (PD) is one of the most common diseases of the central nervous system, primarily affecting the elderly. Its symptoms include tremors, slow movement, muscle stiffness (rigidity), and postural instability.This study aimed to investigate the effect of eight weeks of rebound therapy on balance and quality of life in people with PD.Methods: This was a quasi-experimental research study with pre-test and post-test. Among patients with PD, 24 individuals with severity levels 2 to 3 according to the Unified Parkinson Disease Rating Scale (UPDRS)  were selected using convenience and judgmental sampling and randomly divided into two groups: a rebound therapy group (n=12) and a control group (n=12). The Parkinson's Disease Quality of Life Questionnaire (PDQL) was used to evaluate quality of life levels. The Single Leg Stance (SLS) and Y-Balance Test (YBT-LQ) were used to evaluate static and dynamic balance, respectively. Theintervention group performed eight week exercises (two one-hour weekly sessions Data were analyzed using repeated measures ANOVA at a significance level of 0.05.Results: The post-test quality of life scores in the rebound therapy group significantly higher than the pre-test scores, indicating an increase in quality of life (QoL) for patients (P ≤ 0.05). Additionally, patients' static and dynamic balance in the rebound therapy group significantly improved from the pre-test to the post-test (P ≤ 0.05).Conclusion: The results indicate that eight weeks of rebound therapy can effectively improve balance and quality of life in patients with PD. There fore rebound therapy can be recommended as a complementary rehabilitation method in medical centers to enhance the health of PD patients.